2020
DOI: 10.14744/semb.2020.45389
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bladder diverticulum on the pathophysiology of bladder outlet obstruction: An experimental study in guinea pigs

Abstract: Objectives: This study is the first to urodynamically and histopathologically evaluates the effects of bladder diverticulum (BD) secondary to bladder outlet obstruction (BOO). Methods: Guinea pigs (n=32) weighing 900–1,000 g were divided randomly into four groups: Sham, BD, BOO, and BD combined with BOO. All guinea pigs in the four groups underwent urodynamic evaluation preoperatively and at 1 month postoperatively. The bladders were removed and examined histopathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Although these patients presented with varying symptoms, the predominant one in three (50%) of them was voiding, with an average maximum flow rate (Q max) of seven (range [3][4][5][6][7][8][9][10][11]. Two (33.33%) patients suffered from recurrent urinary tract infections (UTI), and one (16.66%) presented mainly with refractory storage LUTS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these patients presented with varying symptoms, the predominant one in three (50%) of them was voiding, with an average maximum flow rate (Q max) of seven (range [3][4][5][6][7][8][9][10][11]. Two (33.33%) patients suffered from recurrent urinary tract infections (UTI), and one (16.66%) presented mainly with refractory storage LUTS.…”
Section: Resultsmentioning
confidence: 99%
“…The information gained from a urodynamic evaluation is important for counseling the patient on possible outcomes after surgery. A recently performed animal study reported a further reduction in compliance in addition to the effects of pre-existing BOO due to the presence of bladder diverticulum [ 6 ]. As most patients show good improvement with measures tailored to any contributing factors like BOO, this should be addressed first.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Acquired BD are commonly associated with bladder outlet obstruction (BOO), as are benign prostatic hyperplasia and recurrent infections. [ 3 ] Currently, little is known about the diagnosis and treatment of BD, and reports on the efficacy of treating diverticula combined with BOO are limited, [ 4 ] with posterior BD being even rarer. Over the past few years, surgical treatment of BD has been attempted using various approaches, including open, endoscopic, and laparoscopic techniques.…”
Section: Introductionmentioning
confidence: 99%